THORACIC LONGUS NERVE LESION IN A PATIENT WITH ANKYLOSING SPONDYLITIS (Zdravstveni glasnik, 2024)
The paper presents a 33 - year - old patient who has been suffering from ankylosing spondylitis since the age of 28. Pain in his right shoulder and weakness in his right arm developed after more hours of walking with a backpack. The performed procedure diagnosed a lesion of the long thoracic nerve without of sensory damage. Peripheral nerve injuries long thoracic nerve lead to weakness of the muscles -serratus anterior muscle and result in a protrusion of the medial side of the scapula (scapula alata). It is difficult to raise the arm in the shoulder joint above the horizontal line, that is to raise the shoulder from the chest when the arm is extended and pressed against a fixed object in front of the patient. Due to its long, relatively superficial course, long thoracic nerve is susceptible to injury, either through direct trauma or stretching. The long thoracic nerve, also called Charles Bell’s external respiratory nerve, is a rare isolated nerve damage. The nerve is often injured from carrying a load on his shoulder, with supraclavicular and axillary injuries, blows in the neck area. Injury has been reported in almost all sports, usually occurring from a blow to the ribs with an outstretched arm. Long thoracic nerve can be damaged during breast cancer surgery, especially radical mastectomy that involve the removal of axillary lymph nodes. It is a common lesion in spinal surgeries.